Study on Interaction Mechanism of Natural Gas Pipe-Landslide System Reinforced by Micropile Groups Based on Model Test. (20th October 2022) - Guan, Wei; Wu, Honggang; Wu, Daoyong; Tang, Lin; Wei, Hong
Abstract : Natural gas pipeline projects in mountainous areas are inevitably affected by geological disasters such as landslides, which pose a serious threat to the safe operation of pipelines along the routes crossing landslide areas. In this paper, based on a pipe-landslide project in a mountainous area in southwest China, the interaction mechanism and failure evolution process of the landslide-pipeline system reinforced by two kinds of micropiles are studied through indoor large-scale physical model tests, and some suggestions on the support work of the pipe-landslide project are put forward according to the test results. It was found that the deformation process of the engineering system composed of landslide, micropile, and pipeline presents a high degree of synergy under the external force and mainly experiences four stages: initial deformation period, uniform deformation period, accelerated deformation period, and residual deformation period. The bending deformation of the perforated pipe micropile is large at the 1/4 position of the pile top from the pile bottom, and the deformation of the screw micropile near the sliding surface is serious. The pipeline welding port is the weak position of the pipeline; after the failure of the pile, the pipeline interface is first cracked, along the interface position along the two ends of the tear, and finally completely broken. The screw micropile cannot effectively resist the landslide thrust at a large load level, so the risk of pipeline damage is greater. The yield strength and ultimate strength of the perforated pipe micropile are greater than those of the screw micropile, and the perforated pipe micropile can still exert a certain residual resistance after reaching the ultimate bearing capacity, which has a beneficial effect on the reinforcement of the pipeline crossing the landslide system. The research results provide important reference value for landslide-pipeline treatment engineering.